2015
DOI: 10.1007/978-1-4939-3353-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Denervation in Rats

Abstract: Experimental renal sympathetic denervation is a well-established technique. Classically, renal sympathetic denervation is achieved by dorsal rhizotomy. While more recently, direct renal sympathetic denervation is typically applied by stripping all visible renal nerve bundles followed by painting with a solution of 10 % phenol in ethanol to remove the remaining nerves. In clinical settings, a reliable marker of renal sympathetic denervation or renal sympathetic overactivity has not been established. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Renal sympathetic denervation of 11-week-old rats was performed by chemical ablation as described previously [20,21]. Briefly, after anesthetizing the rats with pentobarbital (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Renal sympathetic denervation of 11-week-old rats was performed by chemical ablation as described previously [20,21]. Briefly, after anesthetizing the rats with pentobarbital (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Our selection of phenol mirrors typical strategies for renal artery denervation, which has demonstrated effects beyond 6 months, comparable to the duration of our model follow-up. 31 , 32 However, some conflicting studies have reported evidence of renal artery neural regeneration. 33 Thus, although our investigation of nerve fiber density indicates persistent local denervation, the potential for aortic sympathetic neural regeneration is not completely known.…”
Section: Discussionmentioning
confidence: 99%
“…Stress was applied by placing the rats in a foot shock box with a metal grid floor for 4 h. The electric current was controlled using an electronic device (0.15 mA, 5-30 s with random current). The rats' renal nerve was surgically denervated under anesthesia with 10% chloral hydrate according to previous reports [22]. Foot shock stress was commenced 1 week after the surgery.…”
Section: Chronic Stress Animal Modelmentioning
confidence: 99%